1999
DOI: 10.1046/j.1524-4725.1999.08186.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Excisional Wounds Treated with a Tissue-Engineered Skin (Apligraf)

Abstract: To date, this is the largest experience with a tissue-engineered skin product in acute wounds, and this study suggests that tissue therapy may be safe and useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 10 publications
(12 reference statements)
1
83
0
1
Order By: Relevance
“…30,54 Type I collagen triggers immune reactions in only a low percentage of people, and a simple serologic test can determine whether a patient has it. 55,56 In addition, collagen and HA implants significantly inhibited the growth of bacteria pathogens that cause infections, compared with polylactic-co-glycolic acid implants. 57 However, for a prefabricated bioceramic implants such as HA to fit into a bone cavity, the surgeon needs to machine the graft to the desired shape or carve the surgical site, thus leading to increases in bone loss, trauma, and surgical time.…”
Section: Discussionmentioning
confidence: 99%
“…30,54 Type I collagen triggers immune reactions in only a low percentage of people, and a simple serologic test can determine whether a patient has it. 55,56 In addition, collagen and HA implants significantly inhibited the growth of bacteria pathogens that cause infections, compared with polylactic-co-glycolic acid implants. 57 However, for a prefabricated bioceramic implants such as HA to fit into a bone cavity, the surgeon needs to machine the graft to the desired shape or carve the surgical site, thus leading to increases in bone loss, trauma, and surgical time.…”
Section: Discussionmentioning
confidence: 99%
“…A tissue-engineered, Food and Drug Administration-approved, artificial skin containing fibroblast allografts harvested from neonatal skin samples has been available for treatment of nonhealing ulcers and other cutaneous defects. [25][26][27][28][29] Little or no deleterious immune response to the implanted cells has been documented with this device. 29 Recently, investigators from Japan 30 and South Korea 31 also reported research related to FBC coil embolization.…”
Section: Discussionmentioning
confidence: 99%
“…Although this product does not cause immunological rejection, allogeneic cells of the construct do not survive after one to two months in vivo (Eaglstein et al 1999;Griffiths et al 2004). Hence, Apligraf, which was marketed initially as an organotypic skin substitute, can only be considered as a temporary bioactive dressing.…”
Section: Apligrafmentioning
confidence: 99%